“Fed up with the historical homeland”: Re-emigrating from Israel and creating the image of the “Zionist hell” - G. S. Zelenina (Шаги)
Israeli secret analytical reports from the late 1970s expressed anxiety over the growth of neshira — “dropping out” of Jews who left the Soviet Union on Israeli visas but chose to reside in other Western countries. Neshira went hand in hand with another disturbing phenomenon — yerida, the departure of new Soviet immigrants from Israel to Europe or America, or their return to the Soviet Union. The Soviet press kept reporting about “re-emigrants” with a completely different intonation, as did KGB reports. The article examines negative impressions of Israel as transmitted, perhaps in an aggravated form, by Soviet journalists, and as presented in the ego-documents of new immigrants, future re-emigrants included. The stories of the absorption experience related in the egodocuments and therefore deemed trustworthy confirm the relative authenticity of newspaper reports and reveal that the main reason for disappointment were not financial, climatic or other difficulties, but the attitude of the Israeli bureaucracy and fellow citizens perceived as deliberate humiliation of human dignity. When relating their Israeli experience, former Soviet Jews demonstrated their commitment to familiar values, including a preference for the spiritual over the material (e. g., human dignity over prosperity), and social stratification habits, such as differentiation between educated cultural Jews from the big cities and provincial, or shtetl, Jews.